Past, present, and future research of digital twin for smart manufacturing. Issue 1 (30th December 2021) - Son, Yoo Ho; Kim, Goo-Young; Kim, Hyeon Chan; Jun, Chanmo; Noh, Sang Do
ABSTRACT: In the era of the Fourth Industrial Revolution, there is a growing focus on digital twin (DT) in order to advance toward smart manufacturing. Thus, researchers have conducted numerous studies on DT and extensively developed related technologies. There are many studies that apply and analyse DT to actual manufacturing sites for the realization of a smart factory, but it is necessary to clearly consider which part of DT is applied and what function it performs in manufacturing. As such, this study analysed and classified prior literature based on various phases of product lifecycle management, an application field of DT in manufacturing, and the hierarchy level axis of Reference Architecture Model Industry 4.0, the target scope of DT. Accordingly, this study identified research trends in the past and present as well as analysed and identified the major functions of DT (prototyping, pilot testing, monitoring, improvement, and control). Through a gab study on the inadequate aspects of past and present researches, this study proposes directions for future studies on DT and a system architecture that can perform all the functions of DT. Graphical Abstract: